The stein characterization of M-Wright distributions. Issue 5 (4th July 2019) - da Silva, José Luís; Erraoui, Mohamed
ABSTRACT: In this paper, we use the Stein method to characterize the M -Wright distribution M 1 / 3 and its symmetrization. The Stein operator is associated with the general Airy equation and the corresponding Stein equation is nothing but a general inhomogeneous Airy equation.